Homophily in voting behavior: Evidence from preferential voting. - Coufalová, Lucie; Mikula, Štěpán; Ševčík, Michal (Kyklos, 2023)
Homophily—the preference for people similar in their characteristics—is a strong determinant of many types of human relationships. It affects, for example, whom we marry and potentially also whom we vote for. We use data on preferential voting from eight (1996–2021) Czech parliamentary elections matched with census and administrative data to identify the effect of homophily on voting behavior. The Czech system of preferential voting is well suited to an analysis of homophilic preferences, as it enables us to filter out preferences for political parties and focus solely on candidates' individual background characteristics. We identify the effect of homophily on a sample of 6,844,538 observations from small municipalities that are not likely to be affected by potential electoral list optimization. We find that a 1 % increase in the share of a municipality's population whose education level or age are the same as the candidate's increases the number of preferential votes the given candidate receives by 0.5% or 0.2% respectively. We also find evidence for strong geographical homophily as living in the municipality substantially increases the number of preferential votes a candidate receives.